Guidelines for family caregivers of elderly dependent to at home care. - Neusa Maria Azevedo; Fatima Helena Espirito Santo (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2009)
The currently growth of Brazilian population has caused profound changes in social, political, economic, health system, and family relationships. The family is the focus of attention of the nurse education, representing a link between the elderly and the health service to take care in your home. The aim of this study is to identify which guidelines would be provided to elderly dependent-at-home's family caregivers; describe the daily care of the family home to the elderly. It will be expected to contribute to the systematization of guidelines for family caregivers of dependent-at-home elderly; promoting to client a better care and broadening nurses's scope of work for improvement in efficiency and quality of its services. This study is the project of professional master of nursing care of Federal Fluminense University of Rio de Janeiro, Brasil. Qualitative study with case management; For data collecting it was used techniques such as participant observation and semi structured interviews with elderly people participant in the program of home hospitalization at a general public hospital of Rio de Janeiro. The data information will be submitted to content analysis and further discussion in the light of authors who approach the subject.